Pengaruh Financial Knowledge dan Financial Attitude pada Financial Behavior dengan Financial Capability sebagai variabel Intervening pada Guru SMK Muhammadiyah di Kabuapten Banyuwangi - Sarbini, Sri; Martini, Ni Nyoman Putu; Susbiyani, Arik (Relasi : Jurnal Ekonomi, 2024)
This research aims to find out the influence of Financial Knowledge and Financial Attitude on Financial Behavior with Financial Capability as an Intervening Variable for Muhammadiyah Vocational School Teachers in Banyuwangi Regency. The approach used in this research is a quantitative approach, the type of quantitative research used in this research is explanatory research. The population is 121 teachers so this population number is also used as a sample size so that this research is a census research. The statistical test tool used is WarpLS 7.0. The results of this research are that Financial Knowledge and Financial Attitude towards Financial Behavior with Financial Capability as an Intervening Variable for Muhammadiyah Vocational School Teachers in Banyuwangi Regency have a positive and significant influence, both direct and indirect